2014
DOI: 10.2478/intox-2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

Exposure-dependent variation in cryolite induced lethality in the nontarget insect, Drosophila melanogaster

Abstract: The starting point of toxicity testing of any chemical in an organism is the determination of its Lethal Concentration 50 (LC50). In the present study, LC50 of a fluorinated insecticide cryolite is determined in a non-target insect model, Drosophila melanogaster. Interestingly, the result shows that acute LC50 of cryolite was much greater in comparison to the chronic one in case of Drosophila larvae. Larvae which were exposed to 65,000 to 70,000 µg/ml cryolite through food showed 50% mortality after 18 hours o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…3). In course of the determination of chronic LC50 values, the study also demonstrated results very close to the nature of findings on the effects of a fluoride chemical [13], where the chronic LC50 values for larvae, pupae, and adult flies were much lower compared to that of acute values (Fig 5). The reason behind such observation might be because higher concentrations of this chemical are essential to cause both physical and physiological damage in a short period of time which might result in death of the individuals.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…3). In course of the determination of chronic LC50 values, the study also demonstrated results very close to the nature of findings on the effects of a fluoride chemical [13], where the chronic LC50 values for larvae, pupae, and adult flies were much lower compared to that of acute values (Fig 5). The reason behind such observation might be because higher concentrations of this chemical are essential to cause both physical and physiological damage in a short period of time which might result in death of the individuals.…”
Section: Discussionsupporting
confidence: 79%
“…LC50 determination was performed following the method [13] with some modifications. Different concentrations of flubendiamide (TATA TAKUMI ® , Rallis, India) were made in distilled water, mixed with SDM and poured in Petri dishes (diameter -9 cm) for feeding and maintenance of larvae, pupae, and adult flies.…”
Section: Lc50 Determinationmentioning
confidence: 99%
“…From the LC 50 values [16] and the 28-days survival curves [17], appropriate doses (350, 400 and 500 mg/10 g food) were selected for further studies. These extracts were weighed in dried crystalline form for the methanolic extract and as an oily liquid for the nhexane extract and incorporated into fly food at the appropriate doses.…”
Section: In-vivo Biofilm Inhibition Studiesmentioning
confidence: 99%
“…The starting point in determination of the safety profile of any compound is in the determination of its lethal concentration (in acute or chronic conditions) and also to check other toxicological parameters using experimental animals or insects. Lethal Concentration 50 or LC 50 is a standard measure of toxicity to determine how much of a substance is needed to kill half of a group of experimental organisms in a given time [7]. These preclinical studies must be undertaken before any biologically active substance must be evaluated clinically for therapy.…”
Section: Medicinal Herbs Have Consistently Been Consideredmentioning
confidence: 99%